Case report: 10-year follow-up of a patient with neuronal intranuclear inclusion disease and a literature review - Yoshida, Kenji; Kaga, Tomotsugu; Hosoyama, Sachiko; Niwa, Jun-ichi; Sone, Jun; Mabuchi, Naoki (Frontiers in Neuroscience, 2025)
Neuronal intranuclear inclusion disease (NIID) is a rare, progressive neurodegenerative disease with variable clinical manifestations. High signals on diffusion-weighted imaging (DWI) along the corticomedullary junction (CMJ) are a specific feature of NIID. Only a few reports have observed patients for a long period and demonstrated a relationship between magnetic resonance imaging (MRI) features and clinical manifestations. Herein, we present a case of a patient with NIID who underwent a 10-year brain MRI follow-up study and a literature review. A 78-year-old woman presented with severe cognitive dysfunction and disturbances of consciousness. Her brain MRI DWI signal intensity gradually increased over 10 years, and her cognitive function progressively declined. The DWI signal changes were related to the clinical manifestations in this case. In the literature review, we analyzed patients with NIID by classifying them into subgroups and found that high signals on fluid-attenuated inversion recovery (FLAIR) and DWI were related to dementia. Although high DWI signals along the CMJ are specific to NIID, many patients also show high signals on FLAIR in the deep subcortical white matter. In our literature review, dementia could have some correlation to MRI signals. In our case with longitudinal follow up, the DWI high intensity signal expansion could have correlation to cognitive decline. We found dementia and the dementia progression may have some relation to expansion of DWI with intensity signals from the CMJ to the deep subcortical white matter. Our report highlights that DWI signal changes are strongly correlated with the clinical manifestations of NIID.